The Success of Early Initiation of Breastfeeding in terms of the Level of Knowledge and Family Support at the Prasetya Husada Hospital, Karangploso Malang - Mutmainah; Anggraeni, Suci; Hidajaturrokhmah, Nur Yeny (Journal for Research in Public Health, 2021)
Early Initiation of Breastfeeding (IMD) is the process of allowing a baby to breastfeed itself after birth. The baby is placed on the breast of the mother and the baby himself with all his efforts to find nipples to breastfeed immediately (Yuliarti, 2010). The aim of the study was to determine the relationship between the success of IMD implementation in terms of the level of knowledge and family support in the hospital. Prasetya Husada Karangploso Malang. The research design used analytic observational method with cross sectional approach. The number of respondents was 55 people. The instrument used was a questionnaire. The results of data analysis from statistics show that 44 respondents (80%) have good knowledge of IMD, who provide good support as many as 45 respondent families (81.8%) and the number of IMD is 50 respondents (90.9%). The results of the chis-quare analysis between the knowledge variable and the IMD success variable obtained the p-valute value = 0.002. This means that there is a significant relationship between knowledge about IMD and the successful implementation of IMD. The results of the chisquare analysis between the variable family support and the IMD success variable, the p-valute value = 0.001. This means that there is a significant relationship between family support and the successful implementation of IMD. The relationship between knowledge, family support and the success of IMD can be influenced by the age status where the majority of the majority are early adulthood and can also be influenced by the level of education at which the education level of the respondents is SMA / SMK and also influenced by the parity of the respondents where most of the respondents have multiple parity